PERENCANAAN STRATEGIS SI/TI PADA PERGURUAN TINGGI (STUDI KASUS: STMIK BUMIGORA MATARAM) - Adam Bachtiar; Uswatun Hasanah (Universitas Bumigora, 2017)
In process of implementation information technology and communication, every organization are demanded to produce information technology and communication product that aligned with the perpose of organization. Therefor every organization not only arrange plan of business strategic, but then every organization must arrange plan of IS/IT strategic that appropriate with plan of business strategic organization. This research aims to arrange plan of IS/IT strategic for STMIK Bumigora Mataram. Methods are used in this study is the method of Ward & Peppard. The resulted of this research are strategic plan of IT/IS of STMIK Bumigora Mataram that aligned with its strategic plan. In addition, this research also provides the policy of strategic management IT/SI and the schedule of implementation the IS/IT strategic plan for STMIK Bumigora Mataram.